2019
DOI: 10.3390/min9070455
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Minerals: Structural and Chemical Diversity and Complexity

Abstract: Chemical diversity of minerals containing selenium as an essential element has been analyzed in terms of the concept of mineral systems and the information-based structural and chemical complexity parameters. The study employs data for 123 Se mineral species approved by the International Mineralogical Association as of 25 May 2019. All known selenium minerals belong to seven mineral systems with the number of essential components ranging from one to seven. According to their chemical features, the minerals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 58 publications
(90 reference statements)
1
21
0
Order By: Relevance
“…To quantify the chemical, structural and crystallochemical complexities of Te minerals, a total of pieces of 176 chemical composition data, and 117 data sets on crystal structure were reviewed. The level of structural complexity per atom ( str I G ) and per unit cell ( str I G,total ) [21][22][23][24][25][26] were calculated using the following equations [36]:…”
Section: Chemical Structural and Crystallochemical Complexitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To quantify the chemical, structural and crystallochemical complexities of Te minerals, a total of pieces of 176 chemical composition data, and 117 data sets on crystal structure were reviewed. The level of structural complexity per atom ( str I G ) and per unit cell ( str I G,total ) [21][22][23][24][25][26] were calculated using the following equations [36]:…”
Section: Chemical Structural and Crystallochemical Complexitiesmentioning
confidence: 99%
“…In addition, it was shown that using the concept of mineral systems, it is possible to compare different geological objects with each other in terms of their mineral diversity [29][30][31][32]. Shannon information entropy (chemical and structural complexities) and the concepts of mineral systems have also been applied to mineral evolution as a whole [33][34][35] and to the mineral ecology of selenium minerals, including their diversity and complexities [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach suggested by S.V. Krivovichev [24] and recently successfully implemented in [25,26] allows the factors that influence the symmetry preservation or reduction of uranyl selenite units to be revealed, and it shows which of the multiple blocks plays the most important role in a particular structure formation.…”
Section: Complexity Calculationsmentioning
confidence: 99%
“…This approach, recently developed by S.V. Krivovichev [28][29][30] and successfully implemented in [22,31,32], allowed to compare the structures in terms of their information content and to analyze contributions of various substructural building blocks into the complexity of the whole structure. Structural complexity is a negative contribution to the configurational entropy of a crystalline compound and thus could help to understand and describe the processes of various structures formation in the laboratory and, what is of special interest, in nature.…”
Section: Structural Complexitymentioning
confidence: 99%